Social and sustainable entrepreneurship - Lumpkin, G. T.; Katz, Jerome A. (Bingley, U.K. : Emerald, 2011)
This volume considers the timely issues of social and sustainable entrepreneurship. The chapters consider in depth the issues, problems, contexts, and processes that make entrepreneurial enterprises more social and/or sustainable. Top researchers from a diverse set of perspectives have contributed their latest research on a variety of topics such as the role of entrepreneurial bricolage in generating innovations in a social context (Gundry, Kickul, Griffins, Bacq) and emerging themes in social entrepreneurship education (Thiru). Several chapters tackle lingering definitional issues such as the distinctions between social, sustainable, and environmental entrepreneurship (Dean, Sarason, Neenan), or propose social entrepreneurship research agendas based on key research questions found in prior studies (Gras, Mosakowski, Lumpkin). There are brief histories of social change and their entrepreneurial implications (Kucher; Summers), and frameworks for studying different types of social and sustainable entrepreneurship (Lichtenstein). Each of the chapters, in its own way, addresses the progress and promise of social and sustainable entrepreneurship as a future research domain of growing interest and importance.
An introduction to the special volume on social and sustainable entrepreneurship / G.T. Lumpkin, Jerome A. Katz -- Creating social change out of nothing : the role of entrepreneurial bricolage in social entrepreneurs' catalytic innovations / Lisa K. Gundry, Jill R. Kickul, Mark D. Griffiths, Sophie C. Bacq -- Gaining insights from future research topics in social entrepreneurship : a content-analytic approach / David Gras, Elaine Mosakowski, G.T. Lumpkin -- Human capital and hybrid ventures / Moriah Meyskens, I. Elaine Allen, Candida G. Brush -- Understanding opportunity in social entrepreneurship as paradigm interplay / Monica Diochon, Gabrielle Durepos, Alistair R. Anderson -- Grapes, dimes, salt, and markets : social entrepreneurship and non-violent social change / J. Howard Kucher -- A process model of social intrapreneurship within a for-profit company : first community bank / Donald B. Summers, Bruno Dyck -- Social enterprise education : new economics or a platypus? / Yaso Thiru -- Distinctions not dichotomies : exploring social, sustainable, and environmental entrepreneurship / Neil Thompson, Kip Kiefer, Jeffrey G. York -- What should be the locus of activity for sustainability? : eight emerging ecologies of action for sustainable entrepreneurship / Benyamin B. Lichtenstein -- Thinking'sustainably' : the role of intentions, cognitions, and emotions in understanding new domains of entrepreneurship / Norris Krueger, David J. Hansen, Theresa Michl, Dianne H.B. Welsh.
Mode of access: World Wide Web.
Keywords: Social entrepreneurship; Sustainable development